Transformasi Perpustakaan sebagai Pusat Literasi Keuangan Syariah: Mendorong Kemandirian Pemuda Desa Ciputri - Nugroho, Lucky; Putra, Yananto Mihadi; Kasmo, Arief Bowo Prayoga; Purnama, Adhy; Briandana, Rizki; Jamil, Achmad; Setiany, Erna (Dedikasi : Jurnal Pengabdian Kepada Masyarakat, 2025)
The low level of Islamic economic and financial literacy among the Ciputri Village Youth Organization is challenging to build youth economic independence. This Community Service activity aims to improve understanding and skills of Islamic finance through a community-based education approach, supported by the optimization of the function of the library as a literacy center. The program is carried out through socialization, interactive training, simulation, mentoring, and strengthening the collection of Islamic financial literature in village libraries. The activity results showed a significant increase in participants' understanding, the formation of the Sharia Literacy Ambassador Community, and the increasing role of libraries in supporting Islamic financial education. Key recommendations include ongoing mentoring, digital media development, and cross-sectoral collaboration to maintain the program's sustainability and expand the benefits of this education.